Lived Experiences of Regular Vipassana Meditators in Buddha's Birthland: Perspective from Maslow's Hierarchy of Needs Theory - Lama, Santosh; Aryal, Bhagwan; Joshi, Khagendra Prasad (Journal of Kapan Multiple Campus, 2025)
This study examined the spiritual well-being of regular Vipassana meditators in Lumbini, Nepal, a region revered as the birthplace of Gautam Buddha, through a transcendental phenomenological lens. This study examined how regular meditation enables individuals to grow from within, discovering deeper meaning, inner transformation, and a richer spiritual life, thereby building on Maslow’s concept that transcending the self leads to the most profound human fulfillment. Eight purposefully selected meditators participated in in-depth, semi-structured interviews, allowing their lived experiences to illuminate the intersection of contemplative discipline and spiritual fulfillment. Thematic analysis revealed key experiential patterns, including the purity of the mind and detachment from ego, heightened awareness and present-moment living, meaning, purpose, and a sense of sacred connection, as well as the art of living and self-transcendence. The findings showed that Vipassana helps enhance personal spiritual well-being and connects with the highest stage in Maslow’s framework—self-transcendence. This research adds a culturally based perspective on how meditation can lead to inner freedom and spiritual growth. This study has implications for the overall dimensions of health and policy-making.